Synthesis of trans-resveratrol and rotting control in apples with use of elicitors in post‑harvest - Sautter, Cláudia Kaehler; Storck, Lindolfo; Rizzatti, Mara Regina; Mallmann, Carlos Augusto; Brackmann, Auri (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this study was evaluate the effect of the application of abiotic elicitors of resveratrol in 'Gala' and 'Fuji' apples, and rotting control. The treatment was with ultraviolet irradiation, phosphite andacibenzolar-S‑methyl, applied before controlled atmosphere storage and ozone, applied so intermittently during storage. The storage conditions were: 'Gala' (1.5 kPa O2 and 2.5 kPa CO2, at 0.5±0.1°C by eight months) and 'Fuji' (1.0 kPa O2 and phosphite≥UV‑C irradiation≥ozone. There isn’t correlation between synthesis of trans-resveratrol and rotting control, but the phosphite controlled rot in 'Gala'.
Keywords: Malus domestica; Penicillium; acibenzolar-S‑methyl; phosphite; ozone; UV‑C